Incremental prognostic value of stress echocardiography as an adjunct to exercise electrocardiography after uncomplicated myocardial infarction. Issue 4 (1st April 2001) - Bigi, R; Desideri, A; Galati, A; Bax, J J; Coletta, C; Fiorentini, C; Fioretti, P M
Abstract : OBJECTIVE: To assess the prognostic value of stress echocardiography as an adjunct to exercise electrocardiography in patients with uncomplicated acute myocardial infarction. DESIGN: 496 patients underwent a maximum exercise ECG and pharmacological stress echocardiography (406 dobutamine and 90 dipyridamole) within 15 days of uncomplicated acute myocardial infarction and were followed for a mean of 25 months (range 1–74 months) for reinfarction, unstable angina, and cardiac death. Patients undergoing revascularisation were omitted. RESULTS: Exercise ECG was positive in 162 patients (32.6%) and low threshold positive (< 100 W) in 91 (18%). Stress echocardiography was positive in 239 patients (48%) (194 with dobutamine and 45 with dipyridamole stress). The agreement between the two tests was 63% (κ = 0.24, 95% confidence interval 0.15 to 0.33). Sixty nine spontaneous events occurred (14 cardiac deaths, 26 reinfarctions, and 29 with unstable angina requiring hospital admission), and 126 patients underwent revascularisation (39 coronary angioplasty and 87 bypass surgery). By receiver operating characteristic curve analysis, stress echocardiography provided incremental prognostic information compared with clinical data. A low threshold positive exercise ECG was associated with a worse outcome, but there was a fivefold increase in risk in patients with positive stress echocardiography who also had a high threshold (> 100 W) positive exercise ECG. Event-free survival of patients with both tests positive was significantly less than in patients with only one positive test or with both tests negative. CONCLUSIONS: Stress echocardiography provides additional prognostic information after uncomplicated acute myocardial infarction, but the greatest gain is found in patients with a high threshold positive exercise ECG.